Evidence for divergent endocrine regulation of the murine and ovine GnRH receptor gene promoters - Magee, Christianne; Kouri, Jennifer E.; Cherrington, Brian D.; Cantlon, Jeremy D.; Murtazina, Dilyara A.; Farmerie, Todd A.; Davidsen, Meredith H.; Nett, Terry M.; Clay, Colin M. (Frontiers in Endocrinology, 2025)
Activin, GnRH, and estrogen are key endocrine inputs known to regulate the GnRH receptor (GnRHR) promoter; however, it has become increasingly evident that the mechanisms regulating the GnRHR promoter vary by model and species. To explore these differences, transgenic mice harboring either a wild-type mouse GnRHR (mGnRHR) or sheep (oGnRHR) GnRHR promoter fused to luciferase (-LUC) were infected with an adenovirus overexpressing follistatin, neutralizing activin and decreasing serum concentrations of FSH in both animal models. However, follistatin overexpression in the oGnRHR-LUC mouse more than doubled luciferase expression, whereas in the mGnRHR-LUC animals it led to a 40% decrease in luciferase expression. Thus, the divergent transcriptional responses of the mouse and sheep GnRHR genes to activin appear to be reliably recapitulated in transgenic mice. To further elucidate mechanisms regulating oGnRHR expression, a mouse with a mutated cyclic AMP response element (µCRE) in the proximal oGnRHR-LUC promoter was developed. Using an electrophoretic mobility shift assay, a specific and high affinity interaction of the ovine CRE with nuclear components exists, but these are not modified in the presence of E2, indicating that CRE binding protein (CREB) is necessary but not sufficient to mediate E2 input to oGnRHR expression.